Exploration of Digital Twin Design Mechanism of the Deep in Situ Rock Insulation Coring Device - Bo Yu; Heping Xie; Ling Chen; Wu Zhao; Zhiqiang He (Geofluids)
With the development of the resource exploration and environmental science drilling, strict and scientific requirements are put forward for the samples taken from drilling. It is significant to keep the original appearance of the core and obtain the in situ core for the analysis of deep geological fluid and the exploration of the law of geological disasters caused by large-scale geological exploitation. To achieve the high-fidelity in situ core of deep rock, the development of the corresponding deep in situ fidelity coring device should involve the insulation coring device. The development of deep in situ fidelity coring device is a typical sophisticated product design. There are many problems in the design process, such as multimodules, multidisciplinary, crossdomain, and high coupling, which makes it more difficult for users to participate in product design and understand the product design intention. Digital twin technology, such as time data collection, accelerated iterative optimization, and high-fidelity rendering, provides users with an immersive experience and deepens their understanding of the product design intention. The exploration of the novel design model combined digital twin technology with innovative design theory. Digital twin innovative design of the deep in situ insulation coring device is based on the innovative design method, which built a digital connection between the pre-research test platform and the corresponding simulation models. This digital twin to help users participate in product design and understand the product design process. Finally, the TOPSIS evaluation model was used to calculate the user’s score on the design scheme, which increased by 27.64%, which improves the overall efficiency of product design. This paper provides a practical design method and technical means for the design of the deep in situ insulation coring device based on the geological mechanism and control theory of thermal insulation core.